2008
DOI: 10.1111/j.1471-4159.2008.05718.x
|View full text |Cite
|
Sign up to set email alerts
|

Activity‐dependent expression of ELAV/Hu RBPs and neuronal mRNAs in seizure and cocaine brain

Abstract: Growing evidence indicates that both seizure (glutamate) and cocaine (dopamine) treatment modulate synaptic plasticity within the mesolimbic region of the CNS. Activation of glutamatergic neurons depends on the localized translation of neuronal mRNA products involved in modulating synaptic plasticity. In this study, we demonstrate the dendritic localization of HuR and HuD RNA‐binding proteins (RBPs) and their association with neuronal mRNAs following these two paradigms of seizure and cocaine treatment. Both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
53
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 102 publications
1
53
0
Order By: Relevance
“…Despite the extensive regional variability in the expression of Elavl/Hu proteins 6 in the CNS (Supplementary Figure 1), both HuR and nElavls are present in the hippocampus formation as indicated by the signals detected with anti-HuR and anti-HuD antisera ( Figure 1a); we selected to focus primarily on HuD as a representative of nElavls given prior indications on its involvement in the activity-dependent responses of pyramidal neurons. 7,13 HuR's expression is strong in the CA1 and DG regions, but lower in the CA2/CA3 regions. In contrast, the expression of HuD is strong in the CA2/CA3 regions, but low in the CA1 and DG regions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the extensive regional variability in the expression of Elavl/Hu proteins 6 in the CNS (Supplementary Figure 1), both HuR and nElavls are present in the hippocampus formation as indicated by the signals detected with anti-HuR and anti-HuD antisera ( Figure 1a); we selected to focus primarily on HuD as a representative of nElavls given prior indications on its involvement in the activity-dependent responses of pyramidal neurons. 7,13 HuR's expression is strong in the CA1 and DG regions, but lower in the CA2/CA3 regions. In contrast, the expression of HuD is strong in the CA2/CA3 regions, but low in the CA1 and DG regions.…”
Section: Resultsmentioning
confidence: 99%
“…A considerable body of literature demonstrates the importance of nElavls in neuronal differentiation and the PTR of mRNAs involved in neuronal excitation and synaptic plasticity. [7][8][9][10] On the contrary, HuR was considered as a redundant factor in neurons; recent evidence contradicts this supposition. Genetic ablation and molecular experiments demonstrated that HuR can promote the renewal of neuronal progenitors, whereas in differentiated cells it is silenced by nElavls via the alternative polyadenylation of its mRNA.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…18,19 HuR has ubiquitous tissue expression, but HuB, HuC, and HuD are neuron specific. [20][21][22] HuR stabilizes ARE-mRNAs, such as cfos, 23 against degradation. HuB and HuC function in neuronal differentiation.…”
Section: Introductionmentioning
confidence: 99%